Polish Constitutional Identity and the EU Challenges: European Law as a Tool for the Redrafting of the Polish Constitution - Stępkowski, Aleksander (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
The paper aims at describing, in a synthetic but still systematic way, the impact that EU has for Polish legal system in general and constitutional order in particular. Considering category of the constitutional identity as determined in the jurisprudence of the Polish Constitutional Court, an attempt is made to demonstrate the way in which Polish constitutional order is altered beyond the procedures provided to this end by the Constitution and without proper involvement of the Polish Parliament. It is described, how delegation of certain powers to EU pursuant to specific provisions of the Polish Constitution has profoundly affected domestic balance of power between three branches in at least two different dimensions. However, regardless which dimension is concerned, it always results in the limitation of the powers of national legislature. This process demonstrates also decline of the modern politics and its displacement by its postmodern successor, where real political power is no-longer located on national level, but above, upon supra-national level. Keywords: constitutional identity, Constitutional Court, delegation of powers, limitation of powers, Polish legal order